T2-Weighted-Fluid-Attenuated Inversion Recovery Hyperintensity on Magnetic Resonance Imaging Is Associated With Aggressive Symptoms in Patients With Dural Arteriovenous Fistulas. Issue 9 (September 2019) - Patel, Bhuvic; Chatterjee, Arindam; Petr, Ondra; Collins, Heather; Lanzino, Giuseppe; Derdeyn, Colin P.; Zipfel, Gregory J.
Abstract : Background and Purpose—: Several angiographic factors of dural arteriovenous fistulas (dAVFs) are associated with aggressive presentation and poor natural history. We examined the association of magnetic resonance imaging T2-weighted-Fluid-Attenuated Inversion Recovery (T2/FLAIR) hyperintensity with aggressive presentation. Methods—: A cohort of dAVF patients from 2 centers was retrospectively examined. T2/FLAIR hyperintensity was determined by blinded, de-identified review and compared with angiographic grade and presenting symptoms. Results—: T2/FLAIR hyperintensity was only identified in dAVF patients with cortical venous drainage (CVD). Among patients with CVD, those with T2/FLAIR hyperintensity were more likely to present with aggressive symptoms (20/23, 87.0%) than those without (6/21, 28.5%), P <0.001. All cured dAVFs with symptom resolution and available post-treatment imaging had resolution of T2/FLAIR hyperintensity. Conclusions—: T2/FLAIR hyperintensity strongly correlates with aggressive presentation and CVD in dAVF patients, and may identify a subset that would benefit from early treatment.